The shout-out project : Connecting to community through incursion - Avery, Helen; Vuckovic, Jessica (Agora (Melbourne, Vic.), 2019)
As history teachers, we believe it is imperative to bring history to life for our students, but we know that it is challenging to provide excursions that are relevant and cost- effective, while developing students' historical skills and creating a sense of belonging in their community. The PC Shout-Out Project was an incursion for Year 8 students that took place at Perth College Anglican Girls' School, a K-12 school. The aim of the project was to encourage students to develop their oral history skills and form greater connections with members of the wider community, while engaging with the Positive Psychology that underpins our school's leadership program. The incursion was a three-day multi-disciplinary project in which past Perth College graduates visited the school to be interviewed by the Year 8 students. The students used the interview data to write narratives about interviewees and created artworks that reflected their key strengths. The final process in the project involved sharing the students' creations with their peers and interviewees. We realise that not all teachers will have the luxury of three consecutive days for an incursion, so we also suggest timeline alterations to suit differing schedules. [Author abstract]